Absolute and Body Mass Index Normalized Handgrip Strength Percentiles by Gender, Ethnicity, and Hand Dominance in Americans. Issue 3 (2021) - , Ryan McGrath; , Kyle J. Hackney; , Nicholas A. Ratamess; Vincent, Brenda M.
No abstract available